Performance of Safe Injection Practices by Neonatal Intensive Care Unit Nurses: Associations with Knowledge, Attitudes, and Nursing Professionalism - Mi Hye Seok; Mi-Young Choi (Journal of Fundamental Nursing Science, 2026)
Purpose: This study aimed to identify factors associated with safe injection practice performance among neonatal intensive care unit (NICU) nurses, focusing on safe injection practice knowledge, attitude, and nursing professionalism. Methods: This descriptive study included 120 NICU nurses from six general hospitals in Korea. Data were collected using structured self-report questionnaires from August 1, 2023, to January 30, 2024. Analyses included descriptive statistics, independent t-tests, one-way analysis of variance, the Brown-Forsythe test, Pearson's correlation coefficients, and multiple regression analysis using IBM SPSS Statistics 26.0. Results: Multiple regression analysis showed that attitude toward safe injection practices (β=.54, p